Economic growth, unemployment and skills in South Africa : An Analysis of different recycling schemes of carbon tax revenue - (:unkn) unknown (My University, 2018)
This PhD thesis gives a numerical illustration of how a carbon tax affects South African GDP, employment, CO2 emissions and socio-economic inequality. It uses a “hybrid” computable general equilibrium model of an open economy in a one-step projection from 2005 to 2035. It models second-best economies, notably skill-related rigidities in the labour market and in production of electricity. Seven scenarios for recycling of carbon tax revenue are analysed, plus an option to invest a part of tax revenue in improvement of skills of labour.The analysis shows that under conventional assumptions about technological change, a carbon tax of around 100 ZAR2005 (18 USD2013) per tonne of CO2 will have little negative consequences for GDP and employment, when combined with the right type of tax revenue recycling: Labour subsidies and company profit tax reduction likely lead to the best macro-economic outcomes, though do not reduce inequality. Additional measures are needed to reduce “energy poverty”. To achieve South Africa’s NDC of the Paris Agreement, a carbon tax rate of around 300 ZAR2005 or 55 USD2013 per tonne of CO2 is necessary. However, this could have serious impacts on GDP growth. Also, without a change in the trend of increasing labour productivity, such lower GDP will lead to higher unemployment than in the reference case. An investment in skills of 7.5 billion ZAR2005 of annual Ctax revenue, with the objective of increasing access to high quality education and reducing the high skill labour shortage, if fond to have a very positive impact on GDP growth. However better calibration data is required.The findings of this PhD thesis furthermore call for thorough examination of what type of technological change could be expected for South Africa. Technological progress, consumer preferences and international circumstances limit the economy’s capacity to restructure and decarbonise and therefore to reduce negative consequences of carbon taxation fo
Keywords: African Research